(untitled) (International journal of artificial intelligence, 2025)
The article discusses veterinary and sanitary rules in poultry farming, focusing on evaluating egg quality by examining their weight, shape, and external appearance, particularly the condition of the shell. Information is provided on the "Universal-55" and Chinese "HB-22528" incubators.